Adopting secondary Data is Boon for Accounting Research- Conceptual study - Rengasamy, Dhanuskodi (International Journal of Advanced Scientific Research and Management, 2017)
Secondary data is collected by someone other than the present researcher for current research and originally collected for other purposes. Generally secondary data is publicly available for researchers such as census information, academic publications, statistical agencies etc. Accounting related researches are facing challenge of obtaining valid and reliable primary data. But the availability of secondary data for accounting research is abundant. Many Accounting researches are conducted based on secondary data is called ‘secondary data based accounting research’. Most of the accounting research is related to accounting practices and professions. The objective of this conceptual paper is to describe concepts, advantages, factors and sources of secondary data based accounting research. There is a wide scope of opportunity for conducting research in accounting, based on secondary data. Keywords: Research, accounting research, secondary data, and secondary data based accounting research.